Electrocardiographic changes during therapeutic hypothermia: observational data from a single centre - Jančauskaitė, Dovilė; Samalavičius, Robertas; Glaveckaitė, Sigita; Semėnienė, Palmyra; Šerpytis, Pranas (Acta medica Lituanica, 2020)
Background. Therapeutic hypothermia is recommended to reduce the risk of hypoxic brain damage and improve short-term survival after cardiac arrest. It also temporarily affects the cardiac conduction system. The aim of this study was to evaluate electrocardiographic changes during therapeutic hypothermia and their impact on the outcome. Materials and methods. This retrospective analysis involved 26 patients who underwent therapeutic hypothermia after cardiac arrest in Vilnius University Hospital Santaros Klinikos from 2011 to 2015. Results. During cooling, a significant reduction in the heart rate (p = 0.013), shortening of QRS complex duration (p = 0.041), and prolongation of the QTc interval (p < 0.001) were observed. During the cooling period, five patients had subtle Osborn waves, which disappeared after rewarming. The association between electrocardiographic changes during cooling and unfavourable neurological outcome or in-hospital mortality was non-significant. Conclusions. Therapeutic hypothermia after cardiac arrest causes reversible electrocardiographic changes that do not increase the risk of in-hospital mortality or unfavourable neurological outcomes.
Keywords: therapeutic hypothermia; electrocardiography; Osborn wave; unfavourable neurological outcome; in-hospital mortality